RESPON PERTUMBUHAN BAWANG MERAH (Allium Ascalonicum L) TERHADAP TINGGI KOLOM PASIR SEBAGAI SUMBU DAN MEDIA TANAM SECARA HIDROPONIK - Ahmad Aulia Rahman; Ismed Fachruzi; Fakhrur Razie (Universitas Lambung Mangkurat, 2022)
This study aims to see the response of the sand column as a medium and axis of hydroponic growth of Shallots (Allium ascalonicum L). This research was conducted in the Agroecotechnology Greenhouse from April 2020 to May 2020. The research method used was a one-factor completely randomized design (CRD) with 4 treatments and 4 replications, so that there were 16 experimental units. The 4 treatments used were: P1 = 20 cm, P2 = 25 cm, P3 = 30 cm, P4 = 35 cm. The parameters observed were plant height, leaf number, shallot plants. The results of the research have shown that the treatment of the height of the sand column as the axis and the hydroponic media did not significantly affect all the parameters observed, namely the number of leaves and plant height. In the study, the highest number of leaves was found in treatment p4 (3.84 cm) while for plant height in treatment p3.